(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
The objective of the present work was to create and test a procedure for teaching concepts of Behavior Analysis to teachers, with an emphasis on how to deal with violent student behavior. The study was conducted using 18 members of the teaching staff at a public elementary school in Sao Paulo. The stages of the procedure consisted of: a) a questionnaire about violence; b) a record of teachers’ and students’ behavior; c) observation in the classroom and, d) teacher training. The results show that: a) violence does occur within the medium being studied, and b) an intervention like the one proposed could alter the teacher’s behavior in adequately predicting the outcome of the behavior of his/her students, but the reporting of what happened in the classroom continued as before, even after the training.